Divergent Thinking Moderates the Effect of Conflict and Employment Stress on Employee Performance - Soim; Nik Haryanti; Achmad Choerudin; Imam Saerozi; Siti Marpuah (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
The purpose of this study was to analyze the effect of conflict and work stress on employee performance at the Roudlotul Ulum Jatirejo Islamic Education Foundation. The research method is quantitative. The object of this research is the employees of the Roudlotul Ulum Jatirejo Islamic Education Foundation, totaling 100 people. The data analysis used in the inferential statistical method in this research is partial least squares (PLS). The result of this research were conflict affecting employee performance. This means that higher the conflict, it can affect employee performance. Vice versa, lower the work conflict, but higher the employee's performance. Stress affects employee performance. This means that higher work stress can affect the decrease in employee performance. The results of this study indicate that the work stress that occurs can affect employee performance and vice versa, lower the work stress, and higher the work performance. Divergent thinking mediates conflict in employee performance. However, after this study, divergent thinking weakens the effect of work conflict on employee performance. Work conflicts that often occur are due to differences in perceptions and errors in affection, good communication between employees is needed. This is not meaningful considering that divergent thinking does not have a significant effect on employee performance. Divergent thinking mediates stress on employee performance. This means that divergent thinking skills strengthen the effect of job stress on employee performance. Employees who have good divergent thinking skills are not easy to experience work stress, because they have creative thinking, can solve problems well, act when pressed without considering the risks that will occur, and can contribute to employee performance. Keywords: Divergent Thinking Moderates, Employment Stress, Employee Performance